2017
DOI: 10.1007/s13760-017-0790-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal migraine headache on their children’s quality of life

Abstract: Migraine is an episodic disease characterized by a throbbing and generally unilateral headache, often accompanied by nausea, vomiting and light and sound sensitivity. Migraine is known to affect one's quality of life; not only the person with migraine but also his/her family and social environment are affected by this condition. Our study aimed to evaluate the effects of maternal migraine on children's quality of life. The patient group comprised 70 mothers with migraine diagnoses and their 111 healthy childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…48,51,58,68,78,79,81,88 Parental psychopathology was also associated with poor child responses and stress. 60,65,66,70,[79][80][81]83,91,93 Female children were seen to be at an increased risk of psychiatric disorders, stress, or behavioural problems compared to males in four conditions. [78][79][80]83,89 Multiple sclerosis was the only condition with a recent systematic review, 33 concluding that affected children had generally negative psychosocial experiences.…”
Section: Overview Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…48,51,58,68,78,79,81,88 Parental psychopathology was also associated with poor child responses and stress. 60,65,66,70,[79][80][81]83,91,93 Female children were seen to be at an increased risk of psychiatric disorders, stress, or behavioural problems compared to males in four conditions. [78][79][80]83,89 Multiple sclerosis was the only condition with a recent systematic review, 33 concluding that affected children had generally negative psychosocial experiences.…”
Section: Overview Of Resultsmentioning
confidence: 99%
“…The review identified the use of predominantly crosssectional study designs, which have particular limitations given that child responses are often reported to differ between age groups. 60,78,80 There may also be natural variations at different stages of a child's development, and crosssectional studies might not account for a response that may not be wholly down to parental illness, but due to the more commonplace challenges of growing up.…”
Section: Discussionmentioning
confidence: 99%
“…As is well known, migraine has a negative impact on quality of life 40 . A comparison between mothers with and without migraine demonstrated that mothers with migraine headaches report impaired quality of life and more symptoms of depression and anxiety than a control group 41 . Moreover, maternal characteristics, such as anxiety and depressive symptoms (and, in general, her emotional status), age, and severity of migraine headaches, can negatively affect their children’s quality of life, especially regarding social and school relations.…”
Section: Impact Of Parental Headaches On Their Childrenmentioning
confidence: 95%
“…Women are three times more likely to experience migraine than men, and are predominantly affected during their childbearing years (Burch et al ., 2018). There is growing concern of the long-term mental health problems in the children born to mothers with migraine (Evans et al ., 2005; Kaasbøll et al ., 2012; Güngen et al ., 2017). Children of mothers with migraine had more psychological and behavioural problems that were assessed through questionnaires in several previous studies (Evans et al ., 2005; Kaasbøll et al ., 2012; Güngen et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing concern of the long-term mental health problems in the children born to mothers with migraine (Evans et al ., 2005; Kaasbøll et al ., 2012; Güngen et al ., 2017). Children of mothers with migraine had more psychological and behavioural problems that were assessed through questionnaires in several previous studies (Evans et al ., 2005; Kaasbøll et al ., 2012; Güngen et al ., 2017). It was suggested that maternal migraine may affect offspring psychiatric disorders via altered intrauterine environment in the central nervous system (Burch, 2020).…”
Section: Introductionmentioning
confidence: 99%